HUBUNGAN SKIPPING BREAKFAST DAN OLAHRAGA AEROBIK DENGAN KEJADIAN PRE MENSTRUAL SYNDROME (PMS) PADA MAHASISWI PROGRAM STUDI GIZI PROGRAM SARJANA UPN VETERAN JAKARTA - Untari Puspita Rahmawati (2021)
Pre Menstrual Syndrome (PMS) is a symptom that occurs 6-10 days before menstruation and disappears after menstruation begins or a few days after menstruation. PMS can occur due to hormonal, genetic, chemical, psychological, physical activity and food intake. This study aims to analyze the relationship between skipping breakfast and aerobic exercise with the incidence of pre-menstrual syndrome (PMS) in Universitas Pembangunan Nasional Veteran Jakarta. This study uses a cross sectional study design with a stratified random sampling technique. The sample in this study was 84 respondents. The research data were obtained from filling out questionnaires independently online and using secondary data for body weight and height of the respondents. The results showed that 60.8% experienced moderate to severe PMS symptoms, 54.8% rarely skipped breakfast, and 78.6% rarely did aerobic exercise. The results of the bivariate analysis using the chi-square test showed that there was no relationship between skipping breakfast and the incidence of PMS (p = 0.104). However, there was a relationship between aerobic exercise and the incidence of PMS (p = 0.046). Keywords : Skipping Breakfast, Aerobic Exercise, Pre Menstrual Syndrome (PMS), Youth